Custodire la memoria, contrastare l’oblio. L’eccesso del male e la problematicità del perdono - Lissa, Giuseppe (Bollettino Filosofico, 2016)
This philosophical essay considers the themes of memory and oblivion from a concrete situation: the experience of World War II and Nazism. On the one hand, we need to remember those events, in particular the Shoah, and that means preserve its memory; on the other, it is necessary to counteract the oblivion of those moments. Of course, preserve the memory and fight oblivion are two sides of the same coin. The author traces a path that starts from a personal memory, a visit to Auschwitz, through and interrogating the history of philosophy around the theme of memory, from Plato to Ricoeur, until the most current theoretical considerations, such as the reflection on the European Union. It must be remembered that EU is born from the ashes of Auschwitz, in an attempt to make it impossible that an event like this could happen again. Forget the origin of European Union and desire its end, it means running the risk that Auschwitz could happen again.